2022 31st IEEE International Conference on Robot and Human Interactive Communication (RO-MAN) 2022
DOI: 10.1109/ro-man53752.2022.9900707
|View full text |Cite
|
Sign up to set email alerts
|

Toward the manipulation of time and space in extended reality: a preliminary study on multimodal Tau and Kappa illusions in the visual-tactile domain

Abstract: In the last few years, Extended reality (XR) has enabled novel forms of sensory experiences and social interplay, which can be hardly experienced in real life. However, the full potential of XR has not been exploited yet, since vision remains the main interaction modality, and the time-and spacemodulation of the sense of self -which could open interesting perspectives in several scenarios -is still largely unexplored. To pave the path to a multi-modal manipulation of the sense of time and space in immersive XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In VR, we speculate that the tactile stimuli should improve the sense of immersion while supporting the Kappa effect driven by the visual domain. Another interesting point regards the attention: as opposed to previous experiments 3,5 where participants were alternately asked about time or space, in this study participants were instructed to constantly focus on the intervals' duration. As reported by Polti et al 36 paying attention to time resulted in a lengthened perceived duration, whereas diverting attention away from time shortened it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In VR, we speculate that the tactile stimuli should improve the sense of immersion while supporting the Kappa effect driven by the visual domain. Another interesting point regards the attention: as opposed to previous experiments 3,5 where participants were alternately asked about time or space, in this study participants were instructed to constantly focus on the intervals' duration. As reported by Polti et al 36 paying attention to time resulted in a lengthened perceived duration, whereas diverting attention away from time shortened it.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its relevance in the neuroscience of human perception, only a few studies have investigated the Kappa effect in vision and somatosensation: in particular, Cai et al 3 reported an increase in the Kappa effect by providing visual feedback to bimodal audio-tactile stimulation, therefore supporting the hypothesis that the Kappa effect is dominated by the high spatial acuity of vision. In our former preliminary study, the interaction between the visual (V) and tactile (T) domains for the elicitation of the Kappa effect has been investigated in the forearm through visuo-tactile stimuli finding similar outcomes 5 . Here, we comprehensively characterize the link between time perception and multimodal visual-tactile conditions, also through psychometric functions, within the peripersonal space (PPS) (i.e., at the palm and the forearm).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the Kappa effect elicited through multimodal stimulation has received little attention. This is especially true for what concerns concurrent visual-tactile stimulation [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, we pioneered the investigation of time-space illusions elicited by multimodal visual-tactile stimuli delivered through physical interfaces in the real world. In a preliminary study [13] we compared the Kappa effect in the peripersonal space (PPS) using a wearable device equipped with LEDs and vibrotactile actuators. The study compared unimodal visual (V), tactile (T) and bimodal (VT) stimuli suggesting the presence of the Kappa effect in all modalities.…”
Section: Introductionmentioning
confidence: 99%